Modelling Migration and Regional Labour Markets: An Application of the New Economic Geography Model RHOMOLO - d'Artis Kancs; Andries Brandsma; Damiaan Persyn (European Regional Science Association (ERSA), 2013)
The present paper describes the modelling of regional labour markets in the newly developed dynamic spatial general equilibrium model RHOMOLO, where the labour market equilibrium is determined by firms' labour demand, a wage-curve determining unemployment, and inter-regional labour migration. The RHOMOLO model is parameterised by estimating the key structural parameters econometrically. In order to illustrate the potential of the proposed dynamic spatial general equilibrium approach for analysing regionally integrated labour markets, we carry out simulations showing the effects of a reduction in transportation cost, and assess the impact on regional labour markets. Our results confirm that wages and unemployment are by far the most important channels of adjustment to macro-economic and policy shocks in the EU. In contrast, labour migration plays a secondary role in labour market adjustments in the EU. Our results also suggest that the relationship between market access, labour demand and labour supply is non-linear and spatially inter-dependent, which underlines the importance of the proposed dynamic spatial general equilibrium approach.
Keywords: C68; D58; F22; J20; J61; J64; O15; 330